2019
DOI: 10.1101/694430
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Explicit strategies in force field adaptation

Abstract: In recent years, it has become increasingly clear that a number of learning processes are at play in visuomotor adaptation tasks. In addition to the presumed formation of an internal model of the perturbation, learners can also develop explicit knowledge allowing them to select better actions in responding to a given perturbation. Advances in visuomotor rotation experiments have underscored the important role that such "explicit learning" plays in shaping adaptation to kinematic perturbations.Yet, in adaptatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…We suggest that this generalization arises due to implicit learning mechanisms within the sensorimotor system. Although it has been shown that explicit strategies can play a role in learning visuomotor rotations [30][31][32], studies in force field learning have shown very little contribution of these explicit strategies [33]. Could the participants somehow predict the presence of channel trials and therefore stop to compensate for the force field?…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that this generalization arises due to implicit learning mechanisms within the sensorimotor system. Although it has been shown that explicit strategies can play a role in learning visuomotor rotations [30][31][32], studies in force field learning have shown very little contribution of these explicit strategies [33]. Could the participants somehow predict the presence of channel trials and therefore stop to compensate for the force field?…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the explicit strategy learning and the internal model adaptation is popularly explained by a two-state model of sensorimotor learning with different time scales for each state [11], where the two operate in a 'flat' (non-hierarchical) manner and the net adaptation is defined to be the sum of the two [9,12]. The fast component of the model has been often suggested to be linked to explicit strategy learning in visuomotor rotation tasks [9,10] as well as force field tasks [10,13,14]. On the other hand, recent studies have shown that the TE modulates the adaptation rate of the SPE-driven internal model adaptation [15] or savings [16].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy involves aiming one’s movements towards a surrogate target rather than the true target of the movement. It has been shown that people use re-aiming strategies—or more generally, cognitive strategies—to compensate (at least in part) for visuomotor rotations ( Mazzoni and Krakauer, 2006; de Rugy et al, 2012; Taylor et al, 2014; Morehead et al, 2015 ) and force fields ( Schween et al, 2019 ). In principle, re-aiming enables people to compensate for arbitrary re-mappings of their environment, including large (90°) visuomotor rotations ( Bond and Taylor, 2015 ) or mirror-reversed visual feedback ( Wilterson and Taylor, 2019 ).…”
Section: Introductionmentioning
confidence: 99%